Authentic Projects in Teaching Listening: An Overview of Project-Based Learning (PBL) in Listening for Professional Contexts - Mahmud, Muzdalifah; La Sunra; Syariruddin Dollah (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The study focused on how project-based learning (PBL) is applied as a demonstrative learning method to foster the listening skills of second-year students of the English Language Education Study Program (ELESP) in Universitas Negeri Gorontalo (UNG) for a real-world purpose. This qualitative case study explored the implementation of project-based learning (PBL) to develop listening skills among university students, utilizing classroom observations, student interactions, and document analysis for comprehensive insights. Thematic analysis of classroom observations and document analysis unveiled three significant themes: Critical Listening Competence; Active Engagement and Collaboration; Real-Life Context of Listening Skills The results show that students made considerable progress with their listening skills by utilizing real-world projects that emulate authentic communication situations. Collaborative activities provide opportunities for peer engagement and critical thinking, creating a supportive learning environment. The study also emphasizes that educators need to adapt teaching methods, incorporating technology, and provide a variety of listening resources to prepare students for the complexities of professional listening demands. To address these challenges, recommendations for improving the implementation of PBL, including additional educator’s training and the use of effective assessment tools, were made. In conclusion, the research shows how experiential learning can enhance students’ listening skills.